2006
DOI: 10.2320/matertrans.47.433
|View full text |Cite
|
Sign up to set email alerts
|

Creep Behavior of Extruded Sheets of Magnesium Alloys Containing La-Rich Mischmetal

Abstract: In this study, the effect of RE content on the microstructure and creep properties of Mg-8Al-xRE (x ¼ 0, 1, 2 or 3 mass%) alloys were investigated. The microstructural analysis and phase characterizations of Mg-8Al alloy with 1-3 mass% RE (La-rich Mischmetal) additions were conducted. (i) The as-extruded Mg-8Al-xRE alloys consisted of an -Mg matrix, (Mg 17 Al 12 ) and Al 11 RE 3 compounds. (ii) Raising the extent of RE in the alloy also increases the amount and coarsening of the Al 11 RE 3 compounds, but the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
2
2
0
Order By: Relevance
“…In Mg-3Al alloy, the dispersed Mg 17 Al 12 phase is distributed inside the Mg matrix. A uniformly distributed bright white phase appeared in the Mg-3Al-2.5La alloy (Figure 3b) in rod-like (Al 11 La 3 ) and polygon-type (Al 2 La, Al 2.12 La 0.88 ) shapes, which is consistent with earlier reports [3,21,[25][26][27][28][29]. The brighter second phase in Figure 3c is broken into even finer shapes in the Mg-3Al-2.5La-1.9Y2O3 alloy, especially rod-like shapes, illustrating the ability of Y2O3 nanoparticles to refine the second phases.…”
Section: Microstructural Characterizationsupporting
confidence: 82%
See 1 more Smart Citation
“…In Mg-3Al alloy, the dispersed Mg 17 Al 12 phase is distributed inside the Mg matrix. A uniformly distributed bright white phase appeared in the Mg-3Al-2.5La alloy (Figure 3b) in rod-like (Al 11 La 3 ) and polygon-type (Al 2 La, Al 2.12 La 0.88 ) shapes, which is consistent with earlier reports [3,21,[25][26][27][28][29]. The brighter second phase in Figure 3c is broken into even finer shapes in the Mg-3Al-2.5La-1.9Y2O3 alloy, especially rod-like shapes, illustrating the ability of Y2O3 nanoparticles to refine the second phases.…”
Section: Microstructural Characterizationsupporting
confidence: 82%
“…X-ray diffraction (XRD) studies conducted in the longitudinal direction of the samples are shown in Figure 4. These diffractograms did not reveal the presence of any La phase with Mg, which is consistent with other available reports on Mg-Al-La alloys [8,21,22,[25][26][27][28][29]31,32]. However, they revealed the strong presence of Mg peaks together with the phase comprised of Al 11 La 3 , Al 2 La and Al 2.12 La 0.88 , which are also observed in the SEM micrographs.…”
Section: Microstructural Characterizationsupporting
confidence: 81%
“…The high melting point of these compounds and, thus, their high thermal stability are believed to be responsible for the improved creep resistance of the Mg-Al-Ca [9][10][11] and Mg-Al-RE alloys. [12,13] Similar to Ca and RE, some transition elements such as Zr have high affinity for Al to form Al-Zr compounds. The high thermal stability of these intermetallics may make them a suitable choice for hightemperature applications.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to high thermal stability of mischmetal compound, the addition of La and Ce can increase the hardness, strength and corrosion-resistant of Mg alloys [18][19][20] . In related studies, Jain and Pettersella [21,22] revealed that the significant improvement in the high-temperature tensile creep properties of Mg-Al alloys is due to the formation of the fine rod-like Al 11 RE 3 compound having high thermal stability in the alloys. Moreover, it was reported that the addition of Mm improved slightly the corrosion resistance of AZ91 alloys compared with the addition of Ca [23] .…”
mentioning
confidence: 99%